Positive Versus Negative Framing of Information (Medico Legal Update, 2020)
Background/Objectives: The message is being used as a mode of intervention leading to preventive healthbehaviors and can lead to modifications in knowledge, attitudes and behaviors in a large proportion ofhealth behaviors. The purpose of this study is to identify the effective and persuasive message types amongpositive and negative message types in information on specific health behaviors, to evaluate the effects bysystematically classifying and analyzing related studies and to lead evidence-based practices.Method/Statistical Analysis: In this study, meta-analysis was conducted to evaluate the trends and reportinglevels of the study in order to evaluate and systematically classify the effects of message types in informationon health behavior. Only clinical studies with randomization comparing the effects of positive and negativemessage framing with respect to health behavior were selected. In addition, a case where the interventionswere compared by dividing them into two groups was selected.Improvements/Applications: Among the final selected papers, 7 papers were included in the includedstudies through methodological quality evaluation. Comparison of the positive and negative messageinterventions is related to health behaviors related to breast cancer (SMD -0.04 (95% CI -1.57 to 1.50),health behaviors related to vaccination (MMR, HPV)(SMD 0.20 (95% CI -0.69 to 1.08), cancer screening,vaccination, physical activity and all health activities related to Type 2 diabetes screening (SMD -0.21(95% CI -0.89 to 0.47). All of these were not statistically significant. In order to confirm the change inhealth behavior according to message framing, a study considering the same target population and outcomeindicators is necessary.